Employees’ perceptions of sexual harassment in the hospitality industry: a case of Cresta Jameson Hotel, Harare - Masikuni, Charity (Midlands State University, 2015)
The research sought to analyse employees’ perceptions of sexual harassment at Cresta Jameson Hotel. No study has been done so far in Zimbabwe on employees’ perceptions of sexual harassment. The study aimed at determining the effectiveness of strategies implemented at Cresta Jameson Hotel to deal with sexual harassment. The other objective was to establish the impacts of sexual harassment among employees at Jameson Hotel. The research was a case study and used purposive and convenient sampling. The study population were the managers and non-managerial employees. The study obtained its findings from face to face interviews, company records, journals and text books. The targeted population was 35 employees. The researcher interviewed three managers and 26 non-managerial employees at Cresta Jameson Hotel. The response rate was 84%. It was found that sexual harassment was common at Cresta Jameson Hotel. Males were identified as the main perpetrators of sexual harassment. Employees were afraid of reporting sexual harassment cases as they were ridiculed due to limited confidentiality. The hotel lacked training and adequate policies on sexual harassment. The researcher suggested that hotels should formulate strong sexual harassment policies. There is need to train and retrain employees continuously on sexual harassment. Hotels should encourage employees to report cases of sexual harassment and ensure them of confidentiality. Further research can be undertaken in other hotels in Zimbabwe.